"That's the Point of Going": A Qualitative Inquiry Into the Experiences of Black Males at an Early College High School. Issue 1 (February 2020) - Adams, Tempestt R.; Williams, Brian K.; Lewis, Chance W.
Early college high schools are small schools designed to increase college and career readiness for groups underrepresented in higher education. While some research has focused on student experiences in the early college environment, few have specifically examined the perceptions of Black male students. The purpose of this study was to examine the perceptions of Black males in an early college high school. Using a qualitative case study design, data were collected using focus groups and individual interviews. Emergent themes included students' descriptions of their learning environment and the benefits and challenges they experienced. The results of this study provide further insight into early college high schools and how they serve their targeted population.